Respuestas

2012-04-26T23:57:24+02:00

a-   3/4 (h+18) =1/3

      3/4 h + 27/2 = 1/3

      3/4 h = 1/3 - 27/2

      3/4 h = -79/6

      h = (-79/6) * 4/3

      h = -158/9

b-   5.3 (2x - 2.5) =-3

      10.6x -13.25 = -3

      10.6x = -3 + 13.25

      10.6x = 10.25

       x = 10.25/10.6

       x = 0.97

c-    -4 (y + 4.6) = 3/5

       -4y - 18.4 = 3/5

       -4 y = 3/5 + 18.4

       -4y = 19

       y = 19/(-4)

       y = -4.75

d-    6 (3n + 4) = 2 (n - 11)

       18n + 24 = 2n - 22

       18n - 2n = -22 -24

        16n = -46

        n = -46/16

        n = -23/8 = -2.875